2012
DOI: 10.1021/nn303900y
|View full text |Cite
|
Sign up to set email alerts
|

Pulling Peptides across Nanochannels: Resolving Peptide Binding and Translocation through the Hetero-oligomeric Channel from Nocardia farcinica

Abstract: We investigated translocation of cationic peptides through nanochannels derived from the Gram-positive bacterium Nocardia farcinica at the single-molecule level. The two subunits NfpA and NfpB form a hetero-oligomeric cation selective channel. On the basis of amino acid comparison we performed homology modeling and obtained a channel structurally related to MspA of Mycobacterium smegmatis. The quantitative single-molecule measurements provide an insight into transport processes of solutes through nanochannels.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
70
2
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(79 citation statements)
references
References 40 publications
(94 reference statements)
5
70
2
2
Order By: Relevance
“…The sudden and transient changes in the ionic current elicited by Ang II addition to the cis side resemble the electronic signature of peptides interacting with other biological nanopores 11, 14, 16, 4346 . In-depth analysis of the electronic signature of the transients with the Transalyzer software package 47 was performed for each individual event in terms of average current change during the transient blockage, <I B >, and the dwell time, t D .…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…The sudden and transient changes in the ionic current elicited by Ang II addition to the cis side resemble the electronic signature of peptides interacting with other biological nanopores 11, 14, 16, 4346 . In-depth analysis of the electronic signature of the transients with the Transalyzer software package 47 was performed for each individual event in terms of average current change during the transient blockage, <I B >, and the dwell time, t D .…”
Section: Resultsmentioning
confidence: 84%
“…In contrast, peptide addition into the cis reservoir at −80 mV transmembrane potential yielded frequent and short transient changes in the ionic current (Fig. 1d), indicative of peptide interactions with the open channel 1316, 4246 .…”
Section: Resultsmentioning
confidence: 97%
“…Advances in nanotechnology have enabled the development of nanogap nanopores as improved solid-state nanopores, which were initially created to address mechanical durability issues associated with bionanopores. These nanopore devices have been developed using different materials, 10 e.g., channel proteins for bionanopores 32,[55][56][57] , and graphene 53,58-79 and silicon semiconductor materials 80 for solidstate and nanogap nanopores. Emerging devices based on electric current changes, and not on tunneling currents, have also been proposed.…”
Section: Figurementioning
confidence: 99%
“…32 Selective translocation of peptides has also been explored using the Nocardia farcinica channel, which has a minimum pore diameter of 2 nm or less, and it was revealed that a peptide molecule (oligoarginine) adheres to the nanopore entrance when the electrophoresis voltage is small, while it can be translocated upon the application of a large electrophoresis voltage. 57 Therefore, the effort to identify biopolymers using new channel proteins is underway, and the development of new detection devices based on channel proteins with selective translocation abilities is in the initial stages. Meanwhile, α-hemolysin and MspA are currently being used to develop multi-detection devices.…”
Section: Bionanoporesmentioning
confidence: 99%
“…Both solid-state and protein nanopores applied this strategy to detect targets including BSA, 9-11 streptavidin/avidin, 12, 13 antibodies, 12, 14 and polyarginine peptides. 15 Alternatively, some proteins may be sensed via binding to an auxiliary polymer that threads through the nanopore. 16-18 Because ionic current is sensitive to the size, shape, and surface properties of the analyte protein, as well as analyte-lumen interactions, nanopores are able to distinguish complex protein isoforms, 19-22 e.g.…”
mentioning
confidence: 99%